2008
DOI: 10.1055/s-2008-1043073
|View full text |Cite
|
Sign up to set email alerts
|

Latenzzeit zwischen Exposition und Symptomen bei Allergie gegen Naturlatex: Vorschläge zur Prävention

Abstract: The use of powdered natural rubber latex gloves should be discontinued to prevent the increasing incidence of sensitization to aerogenic latex and to protect those already sensitized from developing allergic bronchial asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Differently from other previous papers which have considered only a subset of baseline measurements, our data include several clinical and functional findings which may be measured in these patients, including also the evaluation of the level of eosinophilic airway inflammation and the pattern of response to SIC. In effect, previous studies have shown that patients with LMWC-induced asthma had a greater duration of exposure to the specific sensitizer before the beginning of asthma symptoms than patients with HMCW-induced asthma [14, 15], or that LMWC asthma showed less frequent sputum eosinophilia [5] or a lower frequency of immediate airway response to SIC [3, 16]. All these data have been confirmed in our study which included a large set of clinical, functional, and biological findings of the disease at the baseline assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Differently from other previous papers which have considered only a subset of baseline measurements, our data include several clinical and functional findings which may be measured in these patients, including also the evaluation of the level of eosinophilic airway inflammation and the pattern of response to SIC. In effect, previous studies have shown that patients with LMWC-induced asthma had a greater duration of exposure to the specific sensitizer before the beginning of asthma symptoms than patients with HMCW-induced asthma [14, 15], or that LMWC asthma showed less frequent sputum eosinophilia [5] or a lower frequency of immediate airway response to SIC [3, 16]. All these data have been confirmed in our study which included a large set of clinical, functional, and biological findings of the disease at the baseline assessment.…”
Section: Discussionmentioning
confidence: 99%